Urgensi Pengawasan dan Pengamatan Terhadap Pelaksanaan Putusan Pengadilan - Phireri Phireri; Johamran Pransisto (Jurnal Litigasi Amsir, 2021)
Supervisory and Observer Judges are regulated in Article 277 of Law Number 8 of 1981 concerning the Criminal Procedure Code, in theory, there is no definition of Supervisory and Observer Judge (Wasmat). This study aims to determine the duties and authorities of the Supervisory and Observer Judges (Wasmat). This study uses a normative type. The results of the research show that the duties and authorities of the Supervisory and Observer Judges are regulated in Articles 277-283 of the Criminal Procedure Code, and the implementation instructions are regulated more clearly in SEMA No. 7 of 1985 which is still in use today. The appointment of Supervisory and Observer Judges is carried out according to the prerogative of the head of the District Court for a term of office of 2 (two) years. Supervisory Judges and Observers conduct/check on the spot (checking on the spot) at least once every 3 (three) months to the Correctional Institution to supervise the truth of the minutes of the implementation of the court decision signed by the Prosecutor, head of the Correctional Institution, and the convict.